PWE-120 Eosinophilic oesophagitis: are we following the protocol on biopsy, histological reporting and management?. (17th June 2017) - Sullivan, A; Hussein, M; Chaudhary, K; Besherdas, K
Abstract : Introduction: Eosinophilic oesophagitis (EoE) is a relatively newly recognised entity. To increase awareness and treatment, the American College of Gastroenterology (ACG) released evidence-based clinical guidelines in 2013 to guide diagnosis and management. We look at three aspects of the guideline: endoscopic and histopathological requirements for diagnosis and pharmacological management, namely proton-pump inhibitor (PPI) and topical steroids. Method: A single centre, retrospective analysis, of patients with a diagnosis of EoE at a large NHS Hospital Trust in north London over 2 years from December 2014 was performed. The database of patients was obtained from the histology department. The endoscopy and histology reports of the patients were analysed for the number of biopsies obtained (protocol recommends 2–4/site), biopsy locations (protocol recommends proximal and distal oesophagus) and presence of ≥15 eosinophils per high powered field (hpf). The management details of patients were obtained from the electronic patient records. Results: 30 patients were identified. 28/30 patients had 2–4 biopsies. Of these 28 patients, 2 (6.7%) clearly had 2–4 biopsies from both proximal and distal oesophagus fulfilling the endoscopic criteria. 15/30 specified the number of eosinophils/hpf. Of which 13/15 (86.7%) had ≥15 eosinophils/hpf and were thus diagnostic for EoE. All of those 15 with no quantified number of eosinophils had their presence mentioned with 3/15 identifying the biopsy as being consistent with EoE without stating the number. 12/30 (40%) had no clear follow up in their clinical records including 6/13 (46.1%) of those with positively diagnosed EoE. 8/28 patients received therapy including a PPI and a topical steroid as per guidelines whilst 7/28 received a PPI alone. Conclusion: Biopsy protocol for diagnosis of EoE falls short of current recommendations, for both the number of oesophageal biopsies obtained and biopsy locations. Only 6.7% have biopsies taken from both proximal and distal oesophagus, thus failing to adhere to ACG guidelines. Histopathologically, only 50% of biopsies had quantified number of eosinophils/hpf. The use of qualitative terms are an inadequate substitute for the quantitative data required for diagnosis. EoE is a histopathological diagnosis so clarity is essential. If biopsy and reporting protocol is not followed there is a risk that patients with another cause of eosinophilia may be misdiagnosed with EoE. There is lack of clear follow up for 40% of patients and of those with follow up a failure to provide the recommended treatment. There is inadequate observance of the ACG guidelines; measures are required to increase adherence. A new equivalent set of guidelines from the British Gastroenterology Society may be of benefit. Disclosure of Interest: None Declared